The effect of race on criminal justice students’ career choices - Tartaro, Christine (American journal of criminal justice, 2003)
This research compares White and Nonwhite criminal justice students in their career goals and reasons for studying criminal justice. Four hundred students from 12 four-year colleges and universities completed surveys for the study. The surveys included several questions about reasons why they chose to major in criminal justice and what the students hoped to achieve in their professional lives. Results of bivariate analyses indicated that students’ career choices do vary by race, but few of these differences remained significant when multivariate models were developed.